1980
DOI: 10.1093/infdis/142.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Intestinal Guanylate Cyclase by Heat-Stable Enterotoxin of Escherichia coli: Studies of Tissue Specificity, Potential Receptors, and Intermediates

Abstract: Heat-stable enterotoxin (ST) of Escherichia coli increased guanylate cyclase activity in homogenates of rat and rabbit intestinal mucosa and stimulated intestinal fluid secretion in suckling mice. The ST effect on guanylate cyclase was dose-dependent, occurred without a time lag, and was confined to the particulate fraction. ST activation of guanylate cyclase was tissue-specific; ST did not alter activity of soluble or particulate rat liver, lung, heart, kidney, or cerebral cortex enzyme. The ST activity on gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(123 citation statements)
references
References 36 publications
7
116
0
Order By: Relevance
“…STa has been shown to bind directly to and stimulate intestinal guanylate cyclase expressed in COS-7 cells (28). A wealth of additional information has shown that the net result of STa binding to sensitive cells or tissue is cGMP production (29,30), such that it appears certain STa directly stimulates guanylate cyclase in vivo. Guanylin represents a natural ligand for the receptor activating the guanylate cyclase/cGMP cascade.…”
Section: Discussionmentioning
confidence: 99%
“…STa has been shown to bind directly to and stimulate intestinal guanylate cyclase expressed in COS-7 cells (28). A wealth of additional information has shown that the net result of STa binding to sensitive cells or tissue is cGMP production (29,30), such that it appears certain STa directly stimulates guanylate cyclase in vivo. Guanylin represents a natural ligand for the receptor activating the guanylate cyclase/cGMP cascade.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs only in intestinal epithelial cells and not in a variety of other tissues and cell lines, suggesting that a unique toxin receptor is present in intestinal cells. The mechanism by which increased cGMP leads to a net secretion of water and electrolytes is not well understood, but the action of ST appears to be mainly anti-absorptive and lacks the secretory activity of LT and cholera toxin Guerrant et al 1980). The fluid secretion induced by STB appears to take place with no alteration of cGMP levels, and the mechanism of action of STB remains unknown (Kennedy et al 1984).…”
Section: Heat-stable Enterotoxin (St)mentioning
confidence: 99%
“…ST induces intestinal secretion by binding to guanylyl cyclase C (GC-C), a single transmembrane protein that is expressed exclusively in the brush border of intestinal epithelial cells from the duodenum to the rectum in adult humans (5)(6)(7)(8)(9)(10). Toxin interaction with the extracellular domain activates the cytoplasmic catalytic domain of GC-C, inducing accumulation of intracellular cGMP ([cGMP] i ; ref.…”
mentioning
confidence: 99%